2014
DOI: 10.1155/2014/329746
|View full text |Cite
|
Sign up to set email alerts
|

Can Tongue Acupuncture Enhance Body Acupuncture? First Results from Heart Rate Variability and Clinical Scores in Patients with Depression

Abstract: Tongue acupuncture (TA) is a method which is not used in western medicine and even in China it is applied very rarely in clinical practice. This study aimed at investigating whether additional TA can improve the efficacy of body acupuncture (BA) in patients with depression. Twenty patients with a mean age of ± SD of 42.9 ± 11.2 years were randomly divided into two groups (n = 10 patients each), one group receiving BA (Zusanli, Sanyinjiao, Neiguan, Shenting, Yintang, and Baihui) and the other receiving BA and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…In contrast, our findings on HRV and TCM-based liver function were not supported by previous experimental studies. A study by Shi et al ( 35 ) suggested that acupuncture treatments targeting acupoints in the liver, heart, and brain—according to TCM—might significantly improve HRV parameters in patients with depression. Another study by Hu Yiting et al ( 36 ) emphasized that the capsules of Shugan Jieyu that target TCM-based liver Qi stagnation significantly improved the standard deviation of NN intervals (SDNN) as well as the low frequency (LF) and the high frequency (HF) of the HRV parameters in individuals with depression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our findings on HRV and TCM-based liver function were not supported by previous experimental studies. A study by Shi et al ( 35 ) suggested that acupuncture treatments targeting acupoints in the liver, heart, and brain—according to TCM—might significantly improve HRV parameters in patients with depression. Another study by Hu Yiting et al ( 36 ) emphasized that the capsules of Shugan Jieyu that target TCM-based liver Qi stagnation significantly improved the standard deviation of NN intervals (SDNN) as well as the low frequency (LF) and the high frequency (HF) of the HRV parameters in individuals with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture not only alleviates autonomic responses by modulating the imbalance between sympathetic and parasympathetic activities but also stabilizes vagal activity in depression (Li et al, 2013;Noda et al, 2015). Several studies have reported that HRV increased significantly in patients with depression after acupuncture or EA (Shi et al, 2013(Shi et al, , 2014. Acupuncture can reduce the risk of PD in patients with depression possibly partly from the modulation of acupuncture for ANS dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Among the interventions implemented in the groups that received acupuncture, 23 64,72) . In addition, in seven studies (15.5%), antidepressants were associated with sham acupuncture (21,27,33,35,37,54,60) ; 12 studies (n = 26.6%) performed only sham acupuncture (25,31,34,43,45,52,53,55,57,59,61,62) ; one study (2.2%) performed acupuncture on the tongue associated with systemic acupuncture 29 ; one study (2.2%) was conducted through home visits (66) ; and one study (2.2%) performed progressive muscle relaxation (63) .…”
Section: Interventions Implemented In the Experimental And Control Gr...mentioning
confidence: 99%